The egg tree : story and pictures - Milhous, Katherine, 1894- (New York, NY : Aladdin Books, 1987)
Katy's Easter morning discovery renews the tradition of the Easter egg tree.
Reprint. Originally published: New York : Scribner, 1950.
Caldecott 1951 Medal Winner
Keywords: Easter -- Fiction; Easter eggs -- Fiction; Pennsylvania Dutch -- Fiction